Pengaruh Pemberian Pupuk Hayati Cair dan Pupuk NPK Terhadap Pertumbuhan Bibit Kelapa Sawit di Pre Nursery - Ebet Stephanus Romunta Sinulingga; Jonatan Ginting; T. Sabrina (Jurnal Agroekoteknologi, 2015)
The aim of the research was to determine the influence of giving liquid biofertilizer and compound fertilizer NPK on the growth of oil palm seedling in pre nursery. The research had been conducted on the land of Agriculture Faculty, Sumatera Utara University, Medan (42 m asl) in February until June 2014, by using Randomized Block Design with two factors, i.e. liquid biofertilizer (0, 5, 10, 15 ml/litre of solvent) and NPK compound fertilizer (0; 2,25; 4,5; 6,75 g/seed). Parameters measured were plant’s height, steem’s diameter, number of leaves, total leaf area, wet shoot weight, wet root weight, dry shoot weight, dry root weight, and the ratio of shoot and root. The results showed that the application liquid biofertilizer with 5 ml/litre of water is better than 0, 10, and 15 ml/litre of water at the same time the application with 2,25 g/seed is better than 0; 4,5; and 6,75 g/seed.Key words : liquid biofertilizer, NPK compound fertilizer, oil palm.